Predator species of thrips (Thysanoptera) associated with avocado orchards in Nayarit, Mexico - Cambero-Campos, Jhonathan; Johansen-Naime, Roberto; García-Martínez, Oswaldo; Cantu-Sifuentes, Mario; Cerna-Chavez, Ernesto; Retana-Salazar, Axel (Instituto de Ecología, A.C., 2011)
The objective of this study was to identify the predaceous thrips species associated with the avocado crop in the state of Nayarit. This research was carried out in four avocado orchards of thecultivars Hass, Choquette and Hall. Weekly samples were taken from January to December, 2008, using the knockdown and net sweeping sampling methods. A total of 294 thrips were identified as predators within 16 species. Franklinothrips vespiformis was the dominant species (21.8%) followed by Lepto-thrips primigenus (21.4%) and F. orizabensis (19.0%), the remaining species collected accounted for 37.8%.